Changing the way we think about change: shifting boundaries changing lives - Isabelle Bartkowiak-Theron
The 2012 Australian and New Zealand Critical Criminology Conference was held in Hobart over two days from 12 - 13 July.   This conference was organised around the theme of ‘Changing the Way We Think about Change – Shifting Boundaries, Changing Lives’. There were five general plenaries, including speakers from Australia, Canada, the United Kingdom, France and the United States, and the conference featured early career as well as experienced researchers. The plenaries included sessions on gender and imprisonment; the pursuit of truth and justice; Indigenous legal needs and justice reinvestment; policing and vulnerability; and migration and global security issues. This publication provides a sample of some of the presentations delivered at the 2012 Critical Criminology Conference